2023
DOI: 10.1111/brv.12985
|View full text |Cite
|
Sign up to set email alerts
|

The rise of hyperabundant native generalists threatens both humans and nature

Abstract: In many disturbed terrestrial landscapes, a subset of native generalist vertebrates thrives. The population trends of these disturbance‐tolerant species may be driven by multiple factors, including habitat preferences, foraging opportunities (including crop raiding or human refuse), lower mortality when their predators are persecuted (the ‘human shield’ effect) and reduced competition due to declines of disturbance‐sensitive species. A pronounced elevation in the abundance of disturbance‐tolerant wildlife can … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
9
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 15 publications
(10 citation statements)
references
References 159 publications
(170 reference statements)
1
9
0
Order By: Relevance
“…Namely, disturbance increases the likelihood of nocturnal detections in rarer specialists’ species and the likelihood of diurnal detections in medium-sized but not large generalist omnivores (behavioural adaptations) and an increase in the absolute number of detections of generalists and their medium-sized predators (species turnover). The large differences in responses of specialists versus generalists aligns well with recent work on tropical forest mammal occupancy and abundance 20 , 38 , 39 . Differences in the magnitude of guild- and species-level shifts may arise, in part, from differential hunting pressure across taxa and locations.…”
Section: Discussionsupporting
confidence: 83%
“…Namely, disturbance increases the likelihood of nocturnal detections in rarer specialists’ species and the likelihood of diurnal detections in medium-sized but not large generalist omnivores (behavioural adaptations) and an increase in the absolute number of detections of generalists and their medium-sized predators (species turnover). The large differences in responses of specialists versus generalists aligns well with recent work on tropical forest mammal occupancy and abundance 20 , 38 , 39 . Differences in the magnitude of guild- and species-level shifts may arise, in part, from differential hunting pressure across taxa and locations.…”
Section: Discussionsupporting
confidence: 83%
“…Mousedeer's relatively high persistence compared to larger herbivores (Amir, Moore, et al, 2022;Amir, Sovie, & Luskin, 2022;Carr et al, 2023) may be due to their small home range of 0.056 km 2 , with reports from forest patches as small as 0.138 km 2 in oil palm-dominated landscapes in northern Sumatra (Luskin, Albert, & Tobler, 2017) and long-term persistence on the 10 km 2 island of Pulau Ubin in Singapore (Chua et al, 2009). Mousedeer persistence but declines in small patches and edges differentiates them from some small omnivorous or frugivorous monkeys and civets whose abundance has increased in the same degraded forests (Dehaudt et al, 2022;Honda et al, 2023;Moore et al, 2023). Such omnivores are often reported to benefit from foraging opportunities in agriculture, which has not been reported for mousedeer.…”
Section: Discussionmentioning
confidence: 99%
“…We tested our second hypothesis using mousedeer counts from published camera trapping studies and analysed this with generalized linear mixed models (glmms). Third, since predators and larger hunted herbivores are often the first to decline in forest edges and fragments (Amir, Moore, et al, 2022;Decoeur et al, 2023;Dehaudt et al, 2022;Dunn et al, 2022;Hendry et al, 2023;Honda et al, 2023;Moore et al, 2023;Nursamsi et al,. 2023), and because mousedeer have been reported from small forest patches, we hypothesized that release from predation and competition would produce a positive association with degraded forests (logged forest, forest edges and forest fragments).…”
Section: Introductionmentioning
confidence: 99%
“…Hilborn and Smith reported that they could not find data supporting a significant decrease in the population of crab-eating macaques and suggested that they have the capacity to increase by 7-10% annually [55]. Moore et al even went as far as to suggest that crab-eating macaques are excessively abundant and pose a threat to natural ecosystems [56]. However, it is also true that many crab-eating macaques are declining due to negative interactions with humans, and human-monkey interactions are on the rise [53,55,57].…”
Section: Discussionmentioning
confidence: 99%